2017
DOI: 10.21010/ajid.v11i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping and Antimicrobial Drug Resistance of Salmonella Isolated From Lettuce and Human Diarrhea Samples in Burkina Faso

Abstract: Background: In Burkina Faso dirty water in particular those of the stoppings and the gutter ones are used for vegetables irrigation in the gardens. The aim of this study was to determine the prevalence and antibiotic susceptibility of Salmonella serotypes from humans and lettuce samples in Burkina Faso. Materials and Methods: Salmonella strains isolated from patients in 2009 to 2015 and lettuce samples in 2014 in Burkina Faso were serotyped using specific antisera. All strains were subjected to a set of 14 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…Antimicrobial susceptibility test showed that all strains were susceptible to the imipenem, which was fully consistent with the study of Eshraghi et al [20]. Also, 80.9% of isolates were resistant to tetracycline which was consistent with findings of Siourimè et al [21]. In our study, with the exception of only one strain (S. enteritidis), all of them (20 isolates; 95.2%) were sensitive to ciprofloxacin, which is almost consistent with the results of Eshraghi et al [20].…”
Section: Resultssupporting
confidence: 91%
“…Antimicrobial susceptibility test showed that all strains were susceptible to the imipenem, which was fully consistent with the study of Eshraghi et al [20]. Also, 80.9% of isolates were resistant to tetracycline which was consistent with findings of Siourimè et al [21]. In our study, with the exception of only one strain (S. enteritidis), all of them (20 isolates; 95.2%) were sensitive to ciprofloxacin, which is almost consistent with the results of Eshraghi et al [20].…”
Section: Resultssupporting
confidence: 91%
“…generated by hospital activities, and these various impacts were identified in the surrounding water bodies [60]. Furthermore, it has been reported in some countries like Benin, Morocco, and Kenya, that hospital wastewater is discharged into community septic tanks due to inappropriate drainage systems [61][62][63].…”
Section: Bacteria Isolated In Community Wastewater and Riversmentioning
confidence: 99%
“…Recovered from river water [57,59], in Enterobacter spp. isolates obtained from seawater [25,48], in Citrobacter spp., E. coli, K. pneumoniae, K. oxytoca and E. cloacae obtained from hospital sewage [53,61,62], in E. cloacae complex, in K. pneumoniae and in R. ornithinolytica isolated from wastewater treatment plants (WWTPs) [53,57,63], and GES-16 producing Acinetobacter spp. and Aeromonas spp.…”
Section: Antibiotic-resistant Bacteria (Gram-negative Bacilli) In Watermentioning
confidence: 99%
“…generated by hospital activities, and these various impacts were identified in the surrounding water bodies [60]. Furthermore, it has been reported in some countries like Benin, Morocco, and Kenya, that hospital wastewater is discharged into community septic tanks due to inappropriate drainage systems [61][62][63].…”
Section: Bacteria Isolated In Community Wastewater and Riversmentioning
confidence: 99%